Surgical Audit of Emergency Ileostomies - Muhammad Zulfiqar Ali, Khalid Munir, Ahmed Zaffar, Muhammad Idrees Anwar (Journal of Rawalpindi Medical College, 2012)
Background: To evaluate the causes and management of emergency ileostomies Methods: In this prospective descriptive study all patients requiring emergency ileostomy were included. Initially patients were resuscitated by administering intravenous fluids and electrolyte replacement. All patients were operated in emergency under general anesthesia. The preoperative indication of ileostomy was noted in all patients. Emergency Laparotomies where primary repair was performed were excluded from the study. Results: Indications for emergency ileostomy creation were the conditions requiring small bowel or proximal colon resection, in which the integrity of a primary anastomosis would be compromised. This was due to a diffuse bowel injury (long-standing peritonitis or obstruction, radiation, Crohn’s disease) creating friable tissues that could not hold a suture. Mean age of the patients was 36+12.59 years with a range of 12-61 years. Most common indication for ileostomy was typhoid intestinal perforation followed by tuberculosis of intestine. Skin excoriation was the most frequent complication noted in ileostomy patients. Conclusion: Infective disease is the most common indication for emergency ileostomy